# Solve each of the

x2 - 2ax - (4b2 - a2) = 0

Using the splitting middle term - the middle term of the general equation is divided in two such values that:

Product = a.c

For the given equation a = 1 b = - 2a c = - (4b2 - a2)

= 1. - (4b2 - a2)

= - (4b2 - a2)

And either of their sum or difference = b

= - 2a

Thus the two terms are (2b - a) and - (2b + a)

Difference = 2b - a - 2b - a

= - 2a

Product = (2b - a) - (2b + a)

( using a2 - b2 = (a + b) (a - b))

= - (4b2 - a2)

x2 - 2ax - (4b2 - a2) = 0

x2 + (2b - a)x - (2b + a)x - (2b - a)(2b + a) = 0

x[x + (2b - a)] - (2b + a)[x + (2b - a)] = 0

[x + (2b - a)] [x - (2b + a)] = 0

[x + (2b - a)] = 0 or [x - (2b + a)] = 0

x = (a - 2b) or x = (a + 2b)

Hence the roots of given equation are (a - 2b) or x = (a + 2b)

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses